Avulsion fracture of peroneus longus at the first metatarsal insertion: a case report. Issue 4 (23rd July 2004) - Murakami, T; Okamura, K; Harada, S; Setojima, M; Ikushiba, Y; Miyamoto, Y; Li, S; Yamada, M
Abstract : Reports of isolated avulsion fracture at the planter lateral base of the first metatarsal without injury of the tarsometatarsal joint are very rare. A 24 year old man sustained an avulsion fracture at the plantar lateral base of the first metatarsal. Normal alignment of metatarsal bones and tarsometatarsal joint was maintained. In this paper, we describe internal fixation of the displaced fragment using x ray and minimally invasive surgery with good results.